UPAYA MENINGKATKAN HASIL BELAJAR IPS MATERI KONDISI ALAM NEGARA-NEGARA DI DUNIA MELALUI METODE TEAM QUIZ: STUDI SMP NEGERI 1 TEMPURAN - S, Supriyatiningsih (Information Technology Education Department, 2023)
This study aims to describe the level of social studies learning outcomes of students in Class IXC SMP Negeri 1 Tempuran after the implementation of the Team Quiz learning method. This research is class action research (PTK). Each cycle consists of three stages of activity, namely planning, implementation of action and observation, and reflection. The subjects of this study were students of class IXC SMP Negeri 1 Tempuran Magelang Regency with a total of 32 students. Data collection in this study used teacher and student activity observation sheets and written tests. Data analysis techniques used were descriptive qualitative and descriptive quantitative with percentages. The results showed the level of learning outcomes of social studies material Natural Conditions of Countries in the World in students of class IXC SMP Negeri 1 Tempuran after the implementation of learning with the Team Quiz method in cycle I on average was 80.38 after cycle II on average was 88.78. Behavioral changes that occur in students of class IXC SMP Negeri 1 Tempuran in the implementation of learning with the Team Quiz method to improve social studies learning outcomes material Natural Conditions of Countries in the World, among others, as follows (a) no students are passive, and able to work together with full responsibility; (b) students are more honest, polite, and disciplined; (c) students are more confident.